How does energy investment affect the energy utilization-growth-tourism nexus? Evidence from E7 Countries. Issue 2 (March 2022) - Gyamfi, Bright Akwasi; Bein, Murad A; Adedoyin, Festus Fatai; Bekun, Festus Victor
Tourism is an important driver of economic growth for several countries in the world. However, the rise in tourism activities has raised concerns regarding emissions resulting from tourist activities such as transportation as well as the consequent effect on the quality of the environment. Hence, this study examines the impact of tourism and other factors such as investments, energy utilization and economic growth on carbondioxide (CO2 ) emission in the emerging industrialized seven countries namely (China, India, Brazil, Mexico, Russia, Indonesia and Turkey) for the period 2000 to 2018. The study uses the Pool Mean Group Autoregressive Distributed Lag (PMG-ARDL), ordinal least square (OLS), dynamic ordinals least square (DOLS) and fully modified least square (FMOLS) estimators as well as Dumitrescu and Hurlin Causality Test. Long run regression estimates reveal that a increase in tourism activities lower carbondioxide emissions in the E7 countries which can be traced to the adoption of environmentally friendly tourism. Furthermore, investment in energy and economic growth, the majority of the regression results point that both factors lower carbondioxide emissions in the emerging seven (E7) countries while energy consumption is a driver of CO2 emissions in the E7 countries. The study suggests that the implementation of environmentally friendly tourism be sustained to continually improve the quality of the natural environment in the blocs. Similarly, strict regulations of economic activities in line with the protection of the environment are advised while the use of renewable energy is needed to reduce emissions in the E7 countries.